Pathogen-host adhesion between SARS-CoV-2 spike proteins from different variants and human ACE2 studied at single-molecule and single-cell levels. Issue 1 (31st December 2022) - Zhang, Xiaoxu; Hong, Bixia; Wei, Peng; Pei, Pengfei; Xu, Haifeng; Chen, Long; Tong, Yigang; Chen, Jialin; Luo, Shi-Zhong; Fan, Huahao; He, Chengzhi
ABSTRACT: The binding of the receptor binding domain (RBD) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein onto human angiotensin-converting enzyme 2 (ACE2) is considered as the first step for the virus to adhere onto the host cells during the infection. Here, we investigated the adhesion of spike proteins from different variants and ACE2 using single-molecule and single-cell force spectroscopy. We found that the unbinding force and binding probability of the spike protein from Delta variant to the ACE2 were the highest among the variants tested in our study at both single-molecule and single-cell levels. As the most popular variants, the Omicron variants have slightly higher unbinding force to the ACE2 than wild type. Molecular dynamics simulation showed that ACE2-RBD (Omicron BA.1) complex is destabilized by the E484A and Y505H mutations and stabilized by S477N and N501Y mutations, when compared with Delta variant. In addition, a neutralizing antibody, produced by immunization with wild type spike protein, could effectively inhibit the binding of spike proteins from wild type, Delta and Omicron variants (BA.1 and BA.5) onto ACE2. Our results provide new insight for the molecular mechanism of the adhesive interactions between spike protein and ACE2 and suggest that effective monoclonal antibody can be prepared using wild type spike protein against different variants.